Faktor-Faktor yang Mempengaruhi Health Related Quality Of Life (HRQoL) pada Pasien Penyakit Jantung Koroner Tanpa Penyakit Terminal - Lubna Farhana; Ramdini, Dwi Aulia; Himayani, Rani; Junando, Mirza (Medula, 2024)
Coronary heart disease (CHD) is a disorder in heart function caused by narrowing of the coronary arteries and atherosclerotic plaque, leading to inadequate oxygen supply to the myocardial muscle. According to the World Health Organization (WHO) data from 2012, CHD is the number 1 cause of death with a percentage of 38.3% of total deaths. Patients with CHD commonly experience symptoms such as chest pain and shortness of breath, which significantly impact in their health-related quality of life (HRQoL). Additionally, complex treatment can also have a broad impact on HRQoL. The aim of this article is to identify the factors influencing HRQoL in CHD patients. In this study, a literature review method was employed, utilizing online databases such as Elsevier, PubMed, Springer. Factors such as social support, comorbidities, lifestyle, disease condition, self-management, and sociodemographic factors are known to influence HRQoL in CHD patients.